Reflexive thematic analysis and men's embodiment following injury or illness: A worked example - Terry G; Hayfield N (Wiley Periodicals LLC on behalf of American Association for Anatomy, 2025)
Reflexive thematic analysis (reflexive TA) originated within psychology and the social sciences and has become an increasingly popular qualitative analytic method across a range of disciplines. In this article, we offer a brief methodological guide for researchers hoping to use the method, suitable for beginners through to those experienced in qualitative research. Reflexive TA can be used to analyze data generated via a range of methods. Reflexive TA is highly flexible, and we outline the choices that researchers need to address when conducting their research. These choices relate to the theoretical approach (realist through to relativist/experiential to critical), their orientation to analyzing the data (inductive to deductive), and the depth in which they analyze their dataset (semantic to latent). We offer an accessible but comprehensive discussion of the six phases of reflexive thematic analysis and how best to produce a rigorous analysis. Starting with familiarization of the dataset as a foundation for analysis, data are then coded, before using these codes to generate initial themes. These early themes are then reviewed and developed, before the researcher moves to defining and naming them. The final phase of analysis is the writing up of the research, at which point final changes may still be made to the results. Written from the basis of our experience of using, teaching, and training reflexive thematic analysis within psychology and the social sciences, we see it as useful for those working across a range of disciplines.
Keywords: bodies; disability; men's health; qualitative research; reflexive thematic analysis